2004
DOI: 10.1007/s10350-003-0111-9
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-inflammatory Drugs and Aspirin for the Prevention of Colorectal Adenomas and Cancer: A Systematic Review

Abstract: There is combined evidence from three randomized trials that aspirin significantly reduced the recurrence of sporadic adenomatous polyps. There was evidence from short-term trials to support regression, but not elimination or prevention, of colorectal polyps in familial adenomatous polyposis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 34 publications
3
39
0
5
Order By: Relevance
“…The PPT investigators later reported that use of nonsteroidal anti-inflammatory drugs (NSAID) reduced the odds of both overall adenoma recurrence (OR, 0.77; 95% CI, 0.63-0.95) and recurrence of advanced polyps (OR, 0.56; 95% CI, 0.31-0.99) (2). This finding was consistent with those reported by randomized trials of adenoma recurrence and results from prospective cohort studies (3,4).…”
Section: Introductionsupporting
confidence: 83%
“…The PPT investigators later reported that use of nonsteroidal anti-inflammatory drugs (NSAID) reduced the odds of both overall adenoma recurrence (OR, 0.77; 95% CI, 0.63-0.95) and recurrence of advanced polyps (OR, 0.56; 95% CI, 0.31-0.99) (2). This finding was consistent with those reported by randomized trials of adenoma recurrence and results from prospective cohort studies (3,4).…”
Section: Introductionsupporting
confidence: 83%
“…Given the lack of randomized controlled trials (RCTs) for most of the risk factors, our model assumptions for the relative risks for risk factors were based on the best estimates available from long-term cohort studies. [23][24][25][26][27][28][29][30][31][32] However, RCTs that estimated the effect of nonsteroidal antiinflammatory drugs on adenoma recurrence 63 showed a smaller effect than what was observed from cohort and case-control studies. Thus, in the current study, we may have overestimated the benefits of risk-factor modification.…”
Section: Discussionmentioning
confidence: 89%
“…4 | 49 role of inflammation in cancer comes from a large number of epidemiological observations, indicating that regular and prolonged treatment with a vast number of synthetic antiinflammatory drugs, including non-steroidal anti-inflammatory drugs (NSAIDs) such as aspirin, can reduce the incidence and recurrence of several human cancers by up to 50% [1,2,3,4,5].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%